Multivariate statistics and contamination factor to identify trace elements pollution in soil around Gerga City, Egypt - Said, I. (2021)
The studied soil ranged from uncontaminated to moderately contaminated with the studied trace elements based on the contamination factor index. The statistical analyses indicated the anthropogenic source of Co, Ni, and Pb as well as the natural source of Mn. The statistical analyses assisted in the discrimination of natural and anthropogenic sources of trace elements in the investigated soil samples. Mn is mainly of natural origin, affected by pedogenic factor, whereas traffic emissions and phosphate fertilizer, as well as domestic activities, are relevant sources of Co, Ni, and Pb elements in the studied soil. Consequently, the recommendation is periodic environmental monitoring and minimizing the fertilization rate.